Functionality comparison of elderly residing in two institutional modalities - Valéria Pagotto; Valéria Alves Pereira da Silva; Lilían Varanda Pereira; Denise Pinheiro Marques Alves dos Santos (Universidade Federal de Goias, 2016)
The objective was to compare the prevalence and factors associated with functional incapacity for BADLs in elderly residing in two institutional modalities. A cross-sectional study with 159 seniors from long term permanence institutions, being 84 resident of Nursing Homes and 75 in Integral Permanence Homes. The functional incapacity (FI) was assessed by the Katz index. The associations were investigated using the χ2 Test or Fisher's exact Test. The prevalence of FI in Nursing Homes was 16.7% (CI 95%: 8.0 - 28.8) and 56.0% (CI 95% 44.2 - 68) in Integral Permanence Homes. In the two institutions, hypertension and cataract were prevalent. In Nursing Homes, it was seen an association between FI and age >80 years and the report of musculoskeletal diseases. Depression was statistically significant in both institutions. The most compromised ADLs were to keep continence, to get dressed and to shower. The findings demonstrate a need of interventions with institutionalized elderly, especially those living in integral permanence modality, focused in depression control.